Pengaruh Pemberian Air Rebusan Temulawak Terhadap Nyeri Dismenorea Pada Siswi Kelas Viii Di Smp Negeri Langgudu Bima Nusa Tenggara Barat Tahun 2023 - Riski Nurfadillah; Syamsuriyati; Sriyana Herman; Julia Fitrianingsih; Bahtiar Baso; Rusli (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Dysmenorrhea can cause disruption of women's activities so that they limit their daily activities, and can also cause them to not concentrate on studying, reluctant to participate in extracurricular activities. and absent from school so that they cannot follow lessons. In Indonesia, according to research by Maisaroh & Proverawati (2012), the incidence of dysmenorrhea occurs around 45-95% in women of productive age. In overcoming dysmenorrhea, pharmacological and non-pharmacological are needed, Non-pharmacological forms are by giving temulawak. Based on research data, it was found that temulawak can relieve pain and pain during menstruation. The purpose of this study was to find the effect of boiled temulawak water to reduce dysmenorrhea in adolescents at SMP Negeri 2 Langgudu. This study used the Quasi Experiment method by looking at the effect of the intervention group and control group treatments, and measuring using the posttest only Control Group Design. It was carried out at SMP Negeri 2 Langgudu. The calculation results showed that the decrease in pain due to dysmenorrhea in the intervention group was 2.7500 at p-value = 0.009 (p